Textual Interpretation and the Development of Chinese Theology - XIE, Wenyu (Journal of Research for Christianity in China (JRCC), 2025)
This article point out that chinese theology construct cannot get out from the west- ern theology. This construct is extension of western theology. The beginning of chinese theol- ogy construct is from the experience of chirstians bible reading and learning from god’s words. The chinese life experience is trained by classic popular books reading. Therefore, con- sidering its form, chinese theology construct is a processing of classic chinese culture material reading in chirstian’s view. During the processing, the became a classic literature of chinese culture. According to the analysis of the difference from chinese culture and western culture about solving concept problem, it shows the connection between theology construct and literature reading.